A review of Energy Efficiency Measures Within Electric Motors Systems. (February 2019) - Trianni, Andrea; Cagno, Enrico; Accordini, Davide
Abstract: Electric motor systems (EMS) play the lion's share in industrial power consumption. Many opportunities for energy efficiency - most of which apparently cost-effective - can be found, but often decision-makers do not take them as the detail for a specific decision can be too high. In many cases, information regarding the characteristics of such energy efficiency measures (EEMs) is quite vague. For this reason, in the present study we offer a thorough overview of EEMs for EMS, basing on an extensive review of scientific and industrial literature, aimed at offering specific detail over single EEMs and thus support to industrial decision-makers. EEMs are presented according to four main groups, as follows: hardware, motor system drives, management of motors in the plant, and power quality. The new categorization could be helpful to support research for the development of a novel framework to represent the main factors the affect the adoption of EMS for EMS.